2014
DOI: 10.1007/s00467-014-2868-6
|View full text |Cite
|
Sign up to set email alerts
|

HLA sensitisation: can it be prevented?

Abstract: Human leukocyte antigen (HLA) sensitisation occurs after transfusion of blood products and transplantation. It can also happen spontaneously through cross-sensitisation from infection and pro-inflammatory events. Patients who are highly sensitised face longer waiting times on organ allocation programmes, more graft rejection and therefore more side effects of immunosuppression, and poorer graft outcomes. In this review, we discuss these issues, along with the limitations of modern HLA detection methods, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 80 publications
2
30
0
1
Order By: Relevance
“…Patients who did not achieve an adequate response to HLA‐selected platelets were tested for HPA antibodies using an in‐house Platelet Immunofluorescence test and a monoclononal antibody immobilised platelet antigen technique . The antibody alloimmunisation status of patients was expressed as cRF%, as previously described . The cRF% was used to try and standardise the calculation of patient HLA reactivity as the cell panels differed between the antibody testing techniques and within each technique over the 4‐year period of the retrospective study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who did not achieve an adequate response to HLA‐selected platelets were tested for HPA antibodies using an in‐house Platelet Immunofluorescence test and a monoclononal antibody immobilised platelet antigen technique . The antibody alloimmunisation status of patients was expressed as cRF%, as previously described . The cRF% was used to try and standardise the calculation of patient HLA reactivity as the cell panels differed between the antibody testing techniques and within each technique over the 4‐year period of the retrospective study.…”
Section: Methodsmentioning
confidence: 99%
“…19 The antibody alloimmunisation status of patients was expressed as cRF%, as previously described. 20 The cRF% was used to try and standardise the calculation of patient HLA reactivity as the cell panels differed between the antibody testing techniques and within each technique over the 4-year period of the retrospective study. Highly sensitised patients with a cRF of >85% were categorised as having a high cRF and patients with a cRF <85% were categorised as low cRF.…”
mentioning
confidence: 99%
“…While transfusion and blood prime avoidance to prevent sensitization/allo‐immunization is optimal, if infants are transfused during HD, transfusion volume should be accounted for in ultrafiltration goals and post‐transfusion hematocrit/hemoglobin should be obtained. It is important to remember that the risk of sensitization is increased in children with previous sensitization events such as failed transplants and recurrent blood transfusions . A study showed even using washed leucodepleted red cells did not reduce the risk of sensitization in children with chronic kidney disease .…”
Section: Part 2 Interpretative Reviewmentioning
confidence: 99%
“…8 Subsequently, this shared protocol was discarded because of the high risk of anti-HLA antibody sensitization and infection. 9 A recent metaanalysis reported that higher rates of anti-HLA antibodies were found in patients with a previous transfusion compared with those without. 10 In pregnancy-sensitized patients, anti-HLA antibodies directed to paternal HLA mismatches were found in 15% to 30% of women, 11 and the immunogenicity of mismatches may be due to the HLA phenotype of the wife and of the husband.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has been suggested that anti-HLA antibodies in patients without a history of known sensitization events were developed in response to cross-reactive epitopes on microorganisms, allergens, and ingested proteins. 9,15,16 The aim of our study was to present the rate of positivity of anti-HLA antibody considering the effect of a single sensitizing event in kidney transplant candidates in the Campania Region (Southern Italy).…”
Section: Introductionmentioning
confidence: 99%